(3TQM GdJfHjgs - (3GHf jhfSs; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdHjhY s
(3BNQgG (B:s
(3jfJgi HHGH ejQGK GdLO hGdENhI , hBNQ eG ajg (B:(3hcGf ddCe GdSOS hddRhL GdfUa hGdHGbi HjfgeG hHjf GdLO , GdePcQ eKd NW GdCfKjjf hGddg CYde HGdUhGH hGdMeO ddg QH GdYGdejf s
(3GdhQbI GdCNjQI HNW eZGjQs
(3Ydi MhGTjgG HYV JUMjMGJs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
Keywords: (3Gdabg GdTGaYjs